Risk factors for healthcare-associated infections and their relationship with waves of the COVID-19 pandemic in an intensive care unit: a nested case-control study - Fernando Gatti de Menezes; Thiago Domingos Corrêa; Bruno de Arruda Bravim; Paula Tuma; Moacyr Silva Júnior; Emy Akiyama Gouveia; Alexandra do Rosário Toniolo; Graziela Geanfrancisco Matta de Paiva; Paula Fernanda Martineli; Helena Maria Fernandes Castagna; Talita Silva Sarro Moraes; Ana Carolina Santiago; et al. (Einstein (São Paulo))
ABSTRACT Objective: To evaluate the risk factors for healthcare-related infections during the COVID-19 pandemic in intensive care units, to investigate the impact of COVID-19 on Central Line-Associated Bloodstream Infection, Catheter-Associated Urinary Tract Infection, and ventilator-associated pneumonia, and to describe healthcare-associated infections in the waves of the COVID-19 pandemic. Methods: This nested case-control study was conducted in a 137-bed adult medical/surgical intensive care unit at a private hospital in São Paulo, Brazil, between January 11, 2019, and May 21, 2022. Case patients were identified using the Nosocomial Infection Control Committee database and control patients were identified using the intensive care unit's EPIMED system. For the analysis of risk factors, the chi-square test, multiple logistic regression model, and Kaplan-Meier method were used to identify independent risk factors, considering p<0.05. Results: The Case Group consisted of 189 healthcare-associated infections, including ventilator-associated pneumonia (61.4%), Central Line-Associated Bloodstream Infection (30.1%), Catheter-Associated Urinary Tract Infection (8.5%), and the Control Group consisted of 6,834 patients. The independent risk factors were COVID-19 infection (OR=2.84, 95%CI=1.92–4.23, p<0.01), length of stay in intensive care greater than 14 days (OR=3.15, 95%CI=1.95–5.14, p<0.01), length of hospital stay greater than 30 days (OR=3.64, 95%CI=2.44–5.51, p<0.01), and patients who were in the third wave (OR=1.72, 95%CI=1.05–2.91, p=0.04). Ventilator-associated pneumonia was the only healthcare-related infection for which COVID-19 infection was an independent risk factor (OR=3.32, 95%CI=1.92–5.94, p<0.01). Conclusion: COVID-19 and length of hospital stay were independent risk factors for healthcare-associated infections, and only ventilator-associated pneumonia was affected by the COVID-19 pandemic.